Examination of the effect of treatment of severe early childhood caries and fluoride varnish applications on salivary oxidative stress biomarkers and antioxidants - Sinem Birant; Sabiha Ceren İlisulu; Hazal Ozcan; Karolin Yanar (BMC Oral Health)
Abstract Background Saliva contains a variety of biochemical compounds, including antioxidants, and serves as the body’s first line of defense against oxidative stress caused by free radicals. The aim of this study was to investigate the effects of dental treatments on salivary oxidative stress biomarkers in children aged 3–5 years with severe early childhood caries (S-ECC) compared to children without caries. Method This study was conducted on 20 children aged 3–5 years with severe early childhood caries (S-ECC) and 20 children without caries. Salivary oxidative stress biomarkers and antioxidants were measured after the initial examination (T0), after the end of restorative treatments (T1), and after fluoride varnish applications (T2). Post hoc Bonferroni test was used to compare normally distributed parameters between T0-T1-T2 times. Pearson correlation analysis was used to examine the relationships between parameters that conform to normal distribution. The Mann-Whitney U test was used to compare the parameters in the control and experimental groups. Significance was evaluated at the p < 0.05 level. Results The mean dmft of the participants in the study group was 8.86 ± 14.5. Advanced oxidation protein products (AOPP), dityrosine (DT), kynurenine (KYN), advanced glycation end products (AGE), lipid hydroperoxides (LHP) and malondialdehyde (MDA) values decrease after the treatment of dental caries and protective fluoride varnish applications, while an increases in total thiol (TSH) and Cu/Zn-superoxide dismutase (Cu/Zn-SOD) values were observed after protective varnish applications compared to pre-treatment values. Antioxidant parameters at time T2 in the study group were statistically significantly higher than in the control group (p < 0.05). In the study group, there was no correlation between TSH and oxidative stress mediators in terms of changes at time T1 post-treatment compared to the pre-treatment period, while an inverse moderate relationship was found with AGE and LHP in terms of changes at time T2 post-treatment (p < 0.05). Conclusions An increase in salivary antioxidants was detected after dental restorations were completed and protective fluoride varnish application, while a decrease in oxidative stress markers was detected. Clinical relevance Fluoride varnish applications applied in the study group may further reduce the oral microbiome load and cause salivary oxidative stress markers to be significantly lower than in the control group.